Court-Martial Jurisdiction: An Expansion of the Least Possible Power - Schlueter, David A (1982)
This article examines the statutory and judicial developments that have apparently expanded military jurisdiction. Serving as the core for this discussion is the amendment to Article 2, UCMJ, and the Court of Military Appeals’ decision in United States v. Trottier, 9 M.J. 337 (C.M.A. 1980), dealing with subject matter jurisdiction of courts-martial over drug-related offenses by service members